Whole-Body Bone Scan Findings after High-Intensity Focused Ultrasound (HIFU) Treatment - Seo, Ye Young; O, Joo Hyun; Sohn, Hyung Sun; Choi, Eun Kyoung; Yoo, Ik Dong; Oh, Jin Kyoung; Han, Eun Ji; Jung, Seung Eun; Kim, Sung Hoon (Nuclear medicine and molecular imaging, 2011)
Purpose This study aims to examine the findings of 99m Tc-diphosphonate bone scans in cancer patients with a history of HIFU treatment. Methods Bone scan images of patients with a history of HIFU treatment for primary or metastatic cancer from January 2006 to July 2010 were retrospectively reviewed. Cases of primary bone tumor or HIFU treatment reaching only the superficial soft tissue layer were excluded. Results Bone scan images of 62 patients (26 female, 36 male; mean age 57 ± 9 years) were studied. HIFU treatment was performed in the liver (n = 40), pancreas (n = 16), and breast (n = 6). Mean interval time between HIFU treatment and bone scan was 106 ± 105 days (range: 1–572 days). Of 62 scans, 43 showed diffusely decreased uptake of bone within the path of HIFU treatment: antero-axillary and/or posterior arcs of right 5th to 11th ribs in 34 cases after treatment of hepatic lesions; anterior arcs of 2nd to 5th ribs in 5 cases after treatment for breast tumors; and posterior arcs of left 9th to 11th ribs or thoraco-lumbar vertebrae in 4 cases after treatment for pancreas tumor. Of 20 patients who had bone scans more than twice, five showed recovered uptake of the radiotracer in the involved ribs in the follow-up bone scan. Conclusion Of 62 bone scans in patients with a history of HIFU treatment for primary or metastatic cancer, 69% presented diffusely decreased uptake in the bone in the path of HIFU treatment.